2013
DOI: 10.1093/hmg/ddt328
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the 3′ untranslated region of FUS causing FUS overexpression are associated with amyotrophic lateral sclerosis

Abstract: Mutations in the gene encoding fused-in-sarcoma (FUS) have been identified in a subset of patients with sporadic and familial amyotrophic lateral sclerosis (ALS). Variants in the 3' untranslated region (3'UTR) of FUS have also been reported in ALS patients, but their pathogenic role has not been assessed. We sequenced the whole 3'UTR of FUS in 420 ALS patients who were negative for mutations in the currently known ALS genes and in 480 ethnically matched controls. We detected four 3'UTR variants (c.*48 G>A, c.*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 27 publications
6
98
0
Order By: Relevance
“…The CAG-FUS WT and CAG-FUS R521G mouse models demonstrate that increased expression of FUS alone can cause cellular toxicity. This result is consistent with the recent finding that mutations in the 3′ UTR of FUS increase FUS expression levels and cause ALS (15). This result is also in agreement with end-stage pathological markers or outcomes in human patients.…”
Section: Differences and Commonalities In Fus Overexpression And Misssupporting
confidence: 93%
See 1 more Smart Citation
“…The CAG-FUS WT and CAG-FUS R521G mouse models demonstrate that increased expression of FUS alone can cause cellular toxicity. This result is consistent with the recent finding that mutations in the 3′ UTR of FUS increase FUS expression levels and cause ALS (15). This result is also in agreement with end-stage pathological markers or outcomes in human patients.…”
Section: Differences and Commonalities In Fus Overexpression And Misssupporting
confidence: 93%
“…Besides missense mutations at the C terminus of FUS protein, overexpression of wild-type FUS caused by mutations in its 3′ UTR also has been linked to ALS (15), suggesting that overexpression of wild-type FUS is pathogenic under certain circumstances. Indeed, pathogenic effects of increased levels of wild-type proteins are common in other neurodegenerative disorders, as exemplified by increased gene dose or overexpression of wild-type TDP-43, α-synuclein, and amyloid β precursor protein (APP) in ALS/FTLD, Parkinson disease, and Alzheimer's disease (16)(17)(18).…”
mentioning
confidence: 99%
“…Nevertheless, the increase in FUS protein did not reach the levels observed with the entire deletion of the 3 0 -UTR (FUS-D3 0 -UTR), suggesting the presence of additional regulatory elements besides the MRE (miRNA recognition element) for miR-141/200a. This seems indeed to be the case since three other mutations, associated with severe ALS phenotypes and linked to high accumulation of protein, were also identified in this region 7 . However, according to TargetScan and PicTar analyses 12,13 , none of those mutations appear to affect conserved miRNA-binding sites.…”
Section: Resultsmentioning
confidence: 73%
“…Bioinformatics search 12,13 for miRNA-responsive elements in the FUS 3 0 -UTR indicated that among the identified 3 0 -UTR mutations 7 , two patients carried the G48A substitution (in one case of inherited type), which localizes to a predicted binding site for miR-141 and miR-200a. These two miRNAs share the same seed sequence and belong to the same miRNA family 14 The members of this family are of particular interest for human health and disease, because they have been shown to be downregulated during tumour progression and to act as key regulators of epithelial-to-mesenchymal transition 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation